Dynamics of the number of saigas of the Volga-Ural population over the past 40 years and factors affecting it - Бегилов, Т.З.; Грачев, Ю.А.; Есжанов, Б.Е. (Fundamental and Experimental Biology, 2023)
In this article, on the basis of historical data, literary sources and personal research of the authors, comparing the Volga-Zhaik saiga population with other saiga populations in the Republic of Kazakhstan, the dynamics of the saiga population in the last 40 years related to the economic development of the territories is analyzed, and the nature of anthropogenic, biotic, genetic, environmental factors is considered. During this period of time, the population of saiga suffered mass extinction due to epizootics several times, from the mid -90s of the 20th century to the mid-2000s, the number decreased sharply and decreased to a dangerous level, and this phenomenon was characteristic of all three populations of saiga in Kazakhstan. The saiga has become an endangered species. Thanks to the alarming of international and republican nature protection organizations and the taking of measures aimed at the protection of saiga by the government of the republic, the number of saiga has increased in recent years, especially the Volga-Zhaik population has recovered. The impact of illegal hunting and pasteurellosis epizootics on the sharp decline of the saiga population in the 2000s was analyzed. It is considered that due to the increase in the population of Volga-Zhaik in the last one or two years, saiga is in strong competition with agriculture and mixing with domestic animals (cattle) in pastures creates the possibility of them spreading various diseases to each other. During the 60s and 90s of the 20th century, when saiga was hunted professionally and their numbers were regulated, the number of all three populations of saiga in Kazakhstan remained stable for many years. The increase in the population of Volga-Zhaik saiga indicates the need to regulate their population.